THE IMPACT OF DAILY PRACTICE FREQUENCY ON STUDENT'S ENGLISH SPEAKING SKILL - Rismayani Marpaung; Nurul Fadilah Tambunan; Tiara Sani Sinaga; Muhammad Ilham Khanis; Didik Santoso (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Speaking is a fundamental skill in learning English as a Foreign Language (EFL). However, despite years of formal instruction, many students continue to experience difficulties in speaking fluently and confidently. Moreover, empirical evidence regarding the benefits of daily English-speaking practice from students' perspectives remains limited. This study aimed to explore students' perceptions of the role of daily English-speaking practice in improving their speaking skills. A quantitative survey design was employed involving 15 students selected through purposive sampling. Data were collected using a structured questionnaire consisting of 15 statements covering pronunciation, fluency, vocabulary mastery, communication effectiveness, self-confidence, motivation, and overall speaking ability. The data were analyzed using descriptive statistics, including frequencies and percentages. The findings revealed that most participants held positive perceptions of daily English-speaking practice, reporting that it improved their pronunciation, fluency, vocabulary, self-confidence, and motivation while reducing their fear of making mistakes during communication. The study concludes that daily English-speaking practice is perceived as an effective strategy for enhancing EFL learners' speaking skills. These findings provide empirical support for integrating regular speaking practice into English language instruction to strengthen learners' communicative competence and improve the quality of EFL speaking instruction. ABSTRAK Berbicara merupakan keterampilan penting dalam pembelajaran Bahasa Inggris sebagai Bahasa Asing (English as a Foreign Language/EFL). Namun, meskipun telah mengikuti pembelajaran formal, banyak siswa masih mengalami kesulitan dalam berbicara secara lancar dan percaya diri. Selain itu, bukti mengenai manfaat praktik berbicara bahasa Inggris setiap hari berdasarkan persepsi siswa masih terbatas. Penelitian ini bertujuan mengeksplorasi persepsi siswa terhadap peran praktik berbicara harian dalam meningkatkan keterampilan berbicara. Penelitian menggunakan desain survei kuantitatif dengan melibatkan 15 siswa yang dipilih melalui purposive sampling. Data dikumpulkan melalui kuesioner berisi 15 pernyataan yang mencakup aspek pelafalan, kelancaran, kosakata, komunikasi, kepercayaan diri, motivasi, dan kemampuan berbicara, kemudian dianalisis menggunakan statistik deskriptif berupa frekuensi dan persentase. Hasil penelitian menunjukkan bahwa mayoritas responden memiliki persepsi positif terhadap praktik berbicara harian karena dinilai mampu meningkatkan pelafalan, kelancaran, penguasaan kosakata, kepercayaan diri, motivasi, serta mengurangi rasa takut melakukan kesalahan saat berkomunikasi. Penelitian ini menyimpulkan bahwa praktik berbicara bahasa Inggris setiap hari merupakan strategi yang dipersepsikan efektif untuk mendukung pengembangan keterampilan berbicara pembelajar EFL serta memberikan dasar empiris bagi penerapan latihan berbicara secara berkelanjutan dalam pembelajaran bahasa Inggris.